Implementasi Pembelajaran Sejarah Kebudayaan Islam Berbasis Al-Quran pada Program Studi Pendidikan Agama Islam di STAI Syekh Manshur Pandeglang - Ela Hikmah Hayati; Jubaedah, Siti; Euis Ernawati (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study aims to analyze the implementation of Islamic Cultural History (SKI) learning based on the Quran in the Islamic Religious Education Study Program (PAI) at STAI Syekh Manshur Pandeglang. The main focus of the study is to examine the methods, challenges, and impacts of integrating the values ​​of the Quran in the SKI curriculum to strengthen students' religious and historical understanding. The study used a qualitative approach with a case study method through participatory observation, in-depth interviews with lecturers and students, and analysis of curriculum documents and teaching materials. The results of the study indicate that the implementation of SKI learning based on the Quran is carried out through a thematic approach, connecting historical events with the verses of the Quran, and linking Islamic cultural values ​​with the current context. The main challenges include limited teaching resources in contextual interpretation of the Quran, variations in students' understanding backgrounds, and the need to develop relevant teaching materials. However, this strategy succeeded in increasing students' learning motivation, deepening their appreciation of Islamic cultural heritage, and strengthening the integration of religious knowledge with history. This study recommends increasing the capacity of lecturers through integrative training, developing contextual Al-Quran-based modules, and optimizing learning technology to support more effective implementation. This finding is an academic contribution in developing a holistic and scripture-based SKI learning model in Islamic religious colleges.